2001
DOI: 10.1105/tpc.13.4.807
|View full text |Cite
|
Sign up to set email alerts
|

A Katanin-like Protein Regulates Normal Cell Wall gBiosynthesis and Cell Elongation

Abstract: Fibers are one of the mechanical tissues that provide structural support to the plant body. To understand how the normal mechanical strength of fibers is regulated, we isolated an Arabidopsis fragile fiber ( fra2 ) mutant defective in the mechanical strength of interfascicular fibers in the inflorescence stems. Anatomical and chemical analyses showed that the fra2 mutation caused a reduction in fiber cell length and wall thickness, a decrease in cellulose and hemicellulose contents, and an increase in lignin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(53 citation statements)
references
References 42 publications
3
50
0
Order By: Relevance
“…The ability to accurately control microtubule number, the rate of microtubule assembly and disassembly, and the assembly of microtubule networks governs cellular processes including differentiation, division and migration. A major regulatory mechanism of dynamic microtubule turnover in eukaryotes, involves microtubule severing by means of AAA-ATPase family proteins including katanin (McNally and Vale, 1993; Burk et al, 2001), fidgetin (Mukherjee et al, 2012) and spastin (Roll-Mecak and Vale, 2005). In plants as represented by the genetically tractable model Arabidopsis thaliana , only katanin has been identified as a microtubule severing protein (Burk et al, 2001; McClinton et al, 2001), and was shown thereon to play central roles in mechanisms governing microtubule organization.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to accurately control microtubule number, the rate of microtubule assembly and disassembly, and the assembly of microtubule networks governs cellular processes including differentiation, division and migration. A major regulatory mechanism of dynamic microtubule turnover in eukaryotes, involves microtubule severing by means of AAA-ATPase family proteins including katanin (McNally and Vale, 1993; Burk et al, 2001), fidgetin (Mukherjee et al, 2012) and spastin (Roll-Mecak and Vale, 2005). In plants as represented by the genetically tractable model Arabidopsis thaliana , only katanin has been identified as a microtubule severing protein (Burk et al, 2001; McClinton et al, 2001), and was shown thereon to play central roles in mechanisms governing microtubule organization.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our data support that microtubule severing is required for transverse microtubule orientation since its initiation in the meristematic cells. Importantly, random microtubule orientation in p60-katanin mutants results in decreased cell length in the fast elongation zone [7, 21] as well as in the meristematic zone [11]. Accordingly, microtubule severing is required throughout all the developmental zones of A. thaliana root, for both the establishment and maintenance of the transverse pattern that underlies anisotropic expansion.…”
Section: Resultsmentioning
confidence: 99%
“…Cortical microtubule organization was studied in wild-type A. thaliana primary roots, in which cells stopped dividing after treatment with aphidicolin, a potent inhibitor of DNA replication [6]. In addition, in order to further investigate the factors involved in microtubule orientation, we compared cortical microtubule arrangement in meristematic root cells of the wild-type and of the p60-katanin mutants fra2 [7], lue1 [8] and ktn1/2 [9]. Our findings support that establishment of transverse cortical microtubule orientation in the meristematic zone of A. thaliana root is substantially associated to cell division and depends on microtubule severing.…”
Section: Introductionmentioning
confidence: 99%
“…in cell wall mutants). Some dwarf mutants ectopically deposit callose (Lukowitz et al , 2001), pectin (His et al , 2001), and the phenolic polymers suberin (Cheng et al , 2000) and lignin (Burk et al , 2001), thereby compromising the stability and flexibility of the cell wall. Treatment of wild-type plants with tunicamycin resulted in the appearance of patches of callose accumulation within the root elongation zone (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%